1993
DOI: 10.1136/vr.133.8.177
|View full text |Cite
|
Sign up to set email alerts
|

Association in bitches between breed, size, neutering and docking, and acquired urinary incontinence due to incompetence of the urethral sphincter mechanism

Abstract: The association in bitches between breed, size, neutering and docking, and acquired incompetence of the urethral sphincter mechanism was investigated. Observational studies were conducted on referred and first-opinion cases of hormonal urinary incontinence and on referred, confirmed cases of incompetence of the urethral sphincter mechanism. Large and giant breeds were at high risk, whereas small breeds were at low risk. Specific breeds at high risk were the old english sheep-dog, rottweiler, dobermann pinscher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
99
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 0 publications
18
99
1
2
Order By: Relevance
“…This result is in agreement with the 3% reported by Holt and Thrusfield (1993) and 6% found by Okkens et al (1997) but is lower than the 12% observed by von Ruckstuhl (1978) and the 20% occurrence rate reported by Arnold et al (1989).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This result is in agreement with the 3% reported by Holt and Thrusfield (1993) and 6% found by Okkens et al (1997) but is lower than the 12% observed by von Ruckstuhl (1978) and the 20% occurrence rate reported by Arnold et al (1989).…”
Section: Discussionsupporting
confidence: 52%
“…An increased incidence of urinary incontinence after spaying has been reported in large and giant breeds (Arnold, 1992;Holt and Thrusfield, 1993), especially in Boxer and Doberman (Arnold, 1992;Nickel et al, 1999). There is evidence that body weight affects the risk of urinary incontinence (Nendick and Clark, 1987;Arnold et al, 1989;Okkens et al, 1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Em 75% das cadelas acometidas, os sinais acontecem durante os primeiros três anos após a cirurgia (ARNOLD et al, 1989). Podem ser encontrados casos de incontinência urinária em animais de todos os tamanhos, porém, o problema parece ser mais comum em cães de médio e grande porte (ARNOLD et al, 1989;HOLT;THRUSFIELD, 1993;ARNOLD, 1999a). Arnold et al (1989) (ARNOLD et al, 1989).…”
Section: Introductionunclassified